Przygotowanie do sakramentu bierzmowania: czy wykorzystana szansa? - Biela, Bogdan (Studia Pastoralne, 2008)
The aim of preparation for Confirmation is the formation for a testimonial form of Christian life and practising of apostolate. In the context of these tasks the present mode of preparation for the reception of the sacrament of Confirmation still remains highly insufficient. This preparation is of a too individualistic and formal character. It does not prepare for living in a community and therefore does not meet its major purpose of fostering Christian maturity. In this context a new meaning should be bestowed upon the roles of witnesses and mystagogy in preparation for the reception of the sacrament of Confirmation. The conclusion is that in pastoral practice one should take into consideration the fuller introduction of the confirmed to a parish life by a catechumenal method. In order to achieve this aim one can use more profoundly the deuterocatechumenal formation of the Light-Life Movement (Ruch Światło-Życie) an experience of the Catholic Charismatic Renewal which is quite efficient in introducing into a reality of faith through seminars of faith renewal. There is also a very valid postulate at stake to create „spirituality centres” in dioceses or special centres preparing adults for Confirmation according to the Rites of Christian initiation of adults (Ordo initiationis christianae adultorum).